Comparison of Core Stability Exercises with Williams’ Flexion Exercises in Patients with Non-Specific low back pain - Zahoor, Idrees Ahmed; Mehmood, Sajid; Rana, Arif Ali; Ghaffar, Noman; Hashim, Muhammad; Wahid, Sidra (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
Low back pain is the most common complaint experienced by the majority of people at some point in their lifetime. Physical therapy has been in favor of effective treatment and prevention of low back pain. However, there is a lack of agreement on the best exercise treatment and abundant studies are in progress. Categorical studies are lacking particularly in this part of the world. This study was designed to compare the effectiveness and efficiency of two specific exercises, core stability exercises with Williams’ flexion exercises, in patients with non-specific low back pain. Objective:The objective of this study was to find out the most effective treatment for patients with non-specific low back pain Methods: This study is a single-blinded randomized clinical trial that was conducted in the physiotherapy outdoor patient department of the public hospital, Jinnah Hospital Lahore (JHL). 20 patients with non-specific low back pain were randomly allocated in two treatment groups, 10 in A (core stability exercises) and 10 in B (Williams’ flexion exercises), after giving informed consent. The conventional treatment of low back pain. e.g. Hot or cold pack, electrotherapeutic modalities was given to the patients of both groups along with their specialized group treatment. The visual analog scale (VAS) and Modified Oswestry Low Back Pain Disability Questionnaire were used before treatment and after the third treatment session during the period of one to two weeks to measure outcomes. The independent samples T-test was used for data analysis. A P-value <0.05 was considered statistically significant Results: The results of this study illustrated that there is a significant difference between the two groups in clinical and therapeutic effect in the reduction of pain as the P-value is <0.05. While the results in the reduction of pain-related disability, measured by the Modified Oswestry Low Back Pain Disability Questionnaire, were not significant as P-value >0.05(P= 0.184). Conclusions: The study indicates that core stability exercises are more effective than Williams’ flexion exercises for the reduction of non-specific low back pain except for a reduction in pain-related disability.